Keunggulan Kompetitif dan Persaingan Pasar Bebas: Peran Moderasi Keputusan Pembelian dalam Perspektif Bisnis Islam - Dwi Fratama, Ikhsan; Fuadi, Fatih; Verawati, Heni (Kartika: Jurnal Studi Keislaman, 2025)
Competitive advantage plays a crucial role in strengthening business positions amidst increasingly dynamic free-market competition. Within the framework of Islamic business, competitive advantage is not only oriented toward attracting consumers but must also adhere to ethical principles and justice. This study aims to examine the influence of competitive advantage on free-market competition, with purchasing decisions positioned as a moderating variable. The research was conducted on 100 respondents who were consumers of Department Store 35 in Gisting, Tanggamus Regency, selected based on predetermined criteria. This study employed a quantitative approach using an online questionnaire distributed through Google Forms, while the data were analyzed with the structural equation modeling (SEM) approach using SmartPLS 4. Moderated regression analysis (MRA) was applied to test the moderating effect. The findings reveal that competitive advantage has a positive and significant impact on free-market competition. Furthermore, purchasing decisions serve as a moderating variable that strengthens the relationship between competitive advantage and free-market competition